2020
DOI: 10.4018/978-1-7998-2128-1.ch007
|View full text |Cite
|
Sign up to set email alerts
|

Linking Corporate Social Responsibility Reporting With the UN Sustainable Development Goals

Abstract: The approval of the 17 Sustainable Development Goals (SDG) within the 2030 United Nations Agenda represents a historic mark for sustainable development, allowing to companies to seek solutions that add value and solve the greatest global challenges, by linking organizational strategies and global priorities. Thus, listed companies will need to be able to assess their impact on the SDGs and review their strategies accordingly. Therefore, reporting can play a key role by informing the progress of listed companie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, in this study it was found that only 23,8% of companies mention the SDGs in their sustainability reports. Monteiro et al (2020) conclude that from a sample of 46 Portuguese listed companies in 2017, none published integrated reports. But 9 of those companies refer to the SDGs in their reports.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in this study it was found that only 23,8% of companies mention the SDGs in their sustainability reports. Monteiro et al (2020) conclude that from a sample of 46 Portuguese listed companies in 2017, none published integrated reports. But 9 of those companies refer to the SDGs in their reports.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…Previous studies indicate companies' size is a determinant factor for SDGs disclosure or SDGsrelated information (Rosati & Faria, 2019a-b;Fonseca & Carvalho, 2019;Pizzi et al, 2021). Additionally, most studies consider listed companies in their samples (Izzo et al, 2020 a-b;Monteiro et al, 2020;van der Waal & Thijssens, 2020;Haywood & Boihang, 2021).…”
Section: Samplementioning
confidence: 99%
“…In the scope of higher education, according to Sepasi et al (2019), empirical research on sustainability/integrated reporting in HEIs is still very embryonic but is even scarcer in the scope of SDG reporting. Empirical research in this topic is limited and largely focused on business sector (Fonseca and Carvalho, 2019;Rosati et al, 2019aRosati et al, , 2019bHaywood and Boihang, 2020;Izzo et al, 2020aIzzo et al, , 2020bMonteiro et al, 2020;Curt o-Page `s et al, 2021;Elalfy et al, 2021;Erin and Bamigboye, 2021;Hummel and Szekely, 2021;Pizzi et al, 2021;Arena et al, 2022;Chagas et al, 2022;Nicolo `et al, 2022). Nowadays, there is some debate on how SDGs should be assessed and reported by HEIs (Aleixo et al, 2020), and some studies have started to explore the integration of SDG in the HEIs' reporting process.…”
Section: Reporting the Sdg In Heismentioning
confidence: 99%